Simultaneous detection of five apple viruses by RT-PCR (International Journal of Biology and Chemistry, 2020)
Apple market takes third place in the world after bananas and grapes. Apple trees are affected by viruses and virus-like diseases, which cause significant economic losses. The most common viruses in the apple tree are Apple chlorotic leafspot virus (ACLSV), Apple stem pitting virus (ASPV), and Apple stem grooving virus (ASGV). Tomato ringspot virus (ToRSV) and apple mosaic virus (ApMV) also cause significant economic losses. Timely detection of viruses and using virus-free planting materials will reduce crop losses. In this work, we performed genetic analysis of ACLSV, ASGV, ASPV, ApMV, ToRSV, and developed RT-PCR test-system for simultaneous detection of these viruses in apple tree materials. The sequences of the developed primers for the test-system are patented. The planting materials imported from Turkey and Italy were investigated for the presence of apple viruses. The most common virus in the samples is ACLSV (60%) followed by ASPV (34%), ASGV (30%) and ApMV (2%). ToRSV virus was not detected at all. Analysis of samples showed that 60% of planting materials were infected with at least one virus, some samples were infected with 3 viruses simultaneously. Mandatory certification of imported planting materials will reduce crop losses of apple orchards.